Contributions of Linqu County Christian Charity Hospital to Healthcare - FENG Xiangke, (Journal of Research for Christianity in China (JRCC), 2025)
This paper attempts to analyze the background of the establishment of the Christian Aide Hospital in Linqu County to clarify its founding purpose. By reviewing its development history, we gain insight into the hospital's current status. Finally, we summarize the hospital's contributions to healthcare.